1999
DOI: 10.1149/1.1392005
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Study of the Formation of  C 60 and  C 70 by Combustion or Pyrolysis

Abstract: An assessment of the available thermodynamic data of gaseous and condensed fullerene C 70 is presented. Gibbs energy minimization of the gaseous C-H-O-Ar chemical system, including large polyaromatic hydrocarbons and the fullerenes C 60 and C 70 , helps to determine under which conditions C 60 and C 70 molecules are stable. The influence of the addition of halogen atoms in the gas phase on the improvement of the yield of these two fullerenes in different conditions is investigated by minimizing the Gibbs energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Recently, Dosa et al invoked a formal Stone−Wales rearrangement in the high-temperature isomerization of angular [3]phenylene . Finally, it should be noted that fullerenes form most likely by different mechanisms under experimental conditions found, for example, in combustion systems, naphthalene pyrolysis, or the recently reported rational chemical synthesis of BF. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Dosa et al invoked a formal Stone−Wales rearrangement in the high-temperature isomerization of angular [3]phenylene . Finally, it should be noted that fullerenes form most likely by different mechanisms under experimental conditions found, for example, in combustion systems, naphthalene pyrolysis, or the recently reported rational chemical synthesis of BF. , …”
Section: Introductionmentioning
confidence: 99%
“…However, Scott and Warren 51 found that the pyracylene hydrocarbon does not rearrange according to the SW pathway at 1100 °C, and Scott stated in a 1996 literature survey that the SW transformation has not been observed at all in a polycyclic aromatic hydrocarbon. 52 tion systems, [54][55][56] naphthalene pyrolysis, 57 or the recently reported rational chemical synthesis of BF. 58,59 Austin et al 17 have generated the SW map for C 60 and have shown that BF is within the same SW family as 1709 of the other unique 1811 fullerene isomers.…”
Section: Introductionmentioning
confidence: 99%
“…(9) and the high activation energy of 188 kJ/moL13) Compared to this value, the above experimental value of 45kJ/mol is much lower, From Eqs. (6) and (7), the low pressure of O2 gas (pO2=0.25) results in slow gas-phase diffusion of O2. Thus, the contribution of gas-phase diffusion to the initial oxidation seems to be responsible for low activation energy.…”
mentioning
confidence: 99%
“…Fullerenes appear in a bellshaped window of thermodynamic stability, limited by polycyclic aromatic hydrocarbons (PAH) at low temperatures (<1500 K) and mainly by acetylene (C 2 H 2 ) at high temperatures (>2500 K). The pressure reduction enlarges this stability area and improves the conversion rates [14,15]. Laser pyrolysis performed at lower pressures could lead to larger fullerene yields, too.…”
Section: Introductionmentioning
confidence: 99%